Ginsenoside Rd Ameliorates Auditory Cortex Injury Associated With Military Aviation Noise-Induced Hearing Loss by Activating SIRT1/PGC-1α Signaling Pathway - Chen, Xue-min; Ji, Shuai-fei; Liu, Yu-hui; Xue, Xin-miao; Xu, Jin; Gu, Zheng-hui; Deng, Sen-lin; Liu, Cheng-dong; Wang, Han; Chang, Yao-ming; Wang, Xiao-cheng (Frontiers in Physiology, 2020)
Free radicals and oxidative stress play an important role in the pathogenesis of noise-induced hearing loss (NIHL). Some ginseng monomers showed certain therapeutic effects in NIHL by scavenging free radicals. Therefore, we hypothesized that Ginsenoside Rd (GSRd) may exert neuroprotective effects after noise-induced auditory system damage through a mechanism involving the SIRT1/PGC-1α signaling pathway. Forty-eight guinea pigs were randomly divided into four equal groups (normal control group, noise group, experimental group that received GSRd dissolved in glycerin through an intraperitoneal injection at a dose of 30 mg/kg body weight from five days before noise exposure until the end of the noise exposure period, and experimental control group). Hearing levels were examined by auditory brainstem response (ABR) and distortion product otoacoustic emission (DPOAE). Hematoxylin-eosin and Nissl staining were used to examine neuron morphology. RT-qPCR and western blotting analysis were used to examine SIRT1/PGC-1α signaling and apoptosis-related genes, including Bax and Bcl-2, in the auditory cortex. Bax and Bcl-2 expression was assessed via immunohistochemistry analysis. Superoxide dismutase (SOD), malondialdehyde (MDA), and glutathione peroxidase (GSH-Px) levels were determined using a commercial testing kit. Noise exposure was found to up-regulate ABR threshold and down-regulate DPOAE amplitudes, with prominent morphologic changes and apoptosis of the auditory cortex neurons (p < 0.01). GSRd treatment restored hearing loss and remarkably alleviated morphological changes or apoptosis (p < 0.01), concomitantly increasing Bcl-2 expression and decreasing Bax expression (p < 0.05). Moreover, GSRd increased SOD and GSH-Px levels and decreased MDA levels, which alleviated oxidative stress damage and activated SIRT1/PGC-1α signaling pathway. Taken together, our findings suggest that GSRd ameliorates auditory cortex injury associated with military aviation NIHL by activating the SIRT1/PGC 1α signaling pathway, which can be an attractive pharmacological target for the development of novel drugs for NIHL treatment.